O racjonalności dydaktyki jako przedmiotu nauczania i jako subdyscypliny pedagogicznej - Mieszalski , Stefan (Studia Edukacyjne, 2018)
Within pedagogical sciences, didactics appears in at least two forms: as a subject taught in higher education and as one of branches of pedagogy. That is why in the field of didactics there is more than one type of rationality; they vary with respect to different purposes of two forms of didactics mentioned above. The main purpose of the article is to analyze some issues related to rationality present in both forms of didactics. In the context of the subject taught in universities, several issues are discussed, e.g. the issue of relationships between structure of didactic content and structure of teacher activities during the teaching process. With respect to didactics as one of the branches of pedagogy, Karl R. Popper’s standpoint is used to discuss the problem of asymmetrical relationships between verification and invalidation of prepositions in the field of didactics.